2022
DOI: 10.1101/2022.05.26.493660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NFYA promotes the malignant behavior of triple-negative breast cancer through the regulation of lipid metabolism

Abstract: Two splicing variants exist in NFYA, which exhibits high expression in many human tumor types, and their expression balance is known to correlate with prognosis in breast cancer, but functional differences are still unclear. Here, we demonstrate that NFYAv1, the long-form variant, upregulates the transcription of ACACA and FASN, essential lipogenic enzymes, to enhance the malignant behavior of triple-negative breast cancer (TNBC). Loss of the NFYAv1-lipogenesis axis strongly suppresses the malignant behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…To investigate the anti-tumor effects of gluconeogenesis regulation by NFYA on HCC, we examined the expression of NFYA and gluconeogenic enzymes in five different HCC cell lines. The expression of NFYA variants was associated with epithelial-mesenchymal transition (EMT) status as reported in breast cancer cells ( Dolfini et al, 2019 ; Okada et al, 2022 ), but no association was observed for the expression of PCK1 and G6PC ( Figure 2A ). PCK1 and G6PC were highly expressed in HepG2 cells, moderately expressed in Hep3B, Huh4, and Huh-7 cells, and barely expressed in SK-Hep1 cells ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…To investigate the anti-tumor effects of gluconeogenesis regulation by NFYA on HCC, we examined the expression of NFYA and gluconeogenic enzymes in five different HCC cell lines. The expression of NFYA variants was associated with epithelial-mesenchymal transition (EMT) status as reported in breast cancer cells ( Dolfini et al, 2019 ; Okada et al, 2022 ), but no association was observed for the expression of PCK1 and G6PC ( Figure 2A ). PCK1 and G6PC were highly expressed in HepG2 cells, moderately expressed in Hep3B, Huh4, and Huh-7 cells, and barely expressed in SK-Hep1 cells ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 57%
“…CUT&RUN experiments were performed as previously described ( Okada et al, 2022 ) with the CUT&RUN assay kit (CST, 86652). In brief, cells were collected 5 h after glucose deprivation treatment, washed, bound to activated Concanavalin A magnetic beads, and permeabilized with antibody binding buffer containing Digitonin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CUT&RUN experiments were performed as previously described (Okada et al, 2022) with the CUT&RUN assay kit (CST, 86652). In brief, cells were collected 5 hours after glucose deprivation treatment, washed, bound to activated Concanavalin A magnetic beads, and permeabilized with antibody binding buffer containing Digitonin.…”
Section: Methodsmentioning
confidence: 99%